Community structure and litter fall density of mangrove stand in Brgy. Ermita, Dumangas, Iloilo. - Sorongon, Joan Abigail Baes (2003.)
The mangrove stand in Brgy. Ermita, Dumangas plays an important role in the protection of the fishponds and serves as a major source of detritus. On 29 December 2002 until 17 February of 2003, a study was conducted to determine the stand structure and litter fall density of the mangrove community. A 10 x 10 m2 plot was used and 12 plots were established in the site. Three species were identified: Avicennia marina, Rhizophora apiculata, and Sonneratia caseolaris. The density of trees was 214 ha-1 ( A. marina 198, R. apiculata 6 and S. caseolaris 9). The density of seedlings was 4,066 seeedlings ha-1 (A. marina 3939, r. apiculata 107, S. caseolaris 21)., Litter production was measured using a 1 m x 1 m x 15 cm litter traps. Eighteen traps were sited beneath the canopy of 18 trees. It was monitored at weekly intervals for a period of 7 weeks. The average litter fall of the site is 3.94 m-2d-1. The mean litter fall of A. marina is 2.04 g m-2d-1, of R. apiculata is 4.69 g m-2d-1 and of S. caseolaris is 5.09 g m-2d-1. ANOVA shows that there is no significant diference between the litter fall densities in the interior and exterior zones.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Mangroves -- Brgy. Ermita, Dumangas, Iloilo